(untitled) (The Pakistan Development Review, 2007)
The Tipping Point is a book about change. What brings on change and why so often it happens so quickly? The book is an intellectual journey taking the reader through the changes in the world of business, education, fashion, and media. It draws heavily from psychology, sociology, history, and epidemiology to explain these changes. The idea of “Tipping Point” is derived from epidemiology. It is the moment in any epidemic when the disease reaches its critical mass—the moment on the graph when the line shoots vertically upwards. Gladwell applies the same idea to “social epidemics”, and tries to figure out “tipping points” in business, social policy, advertisement, TV programming, and a number of other non-medical areas.